The Effects of Lead (Pb) Exposure to Blood Pb Concentration and Hemoglobin Levels in Book Sellers and Street Vendors of Surakarta - Khotijah, Khotijah; Sjarifah, Ipop; Mahendra, Putu Gede Oka; Widyaningsih, Vitri; Setyawan, Haris (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Anemia is still a public health problem in the world and in Indonesia. WHO (2008) reported more than 75% of anemia in Asia is iron deficiency and 63.5% anemia in Indonesia is caused by lack of nutrition. Previous studies described that lead (Plumbum /Pb) can decrease hemoglobin levels. Sriwedari markets’ book sellers and Solo Wholesale Center’s street vendors are susceptible populations exposed to Pb as a result of motor vehicle exhaust. Approximately 70% of Pb in vehicle exhausts emissions are emitted into the air. This study aimed to analyze the effects of Pb exposure on blood Pb concentration and hemoglobin levels. This study was a quantitative observational analytic study with cross sectional design conducted in 2015-2016 at Sriwedari Market. Samples were 97 respondents obtained through random sampling and Spearman correlation was used for data analysis. Result showed that there were association between Pb exposure in the air and blood Pb levels (p=0,000; r=0,606) and blood Pb levels and hemoglobin levels (p=0,000; r=-0,623)